The Dark Side of Social Media: Analysing Dark Pattern Combinations and Their Impacts - Hansika Ukgoda (Universitas Sebelas Maret, 2024)
In today’s digital era, technology is essential in daily life, transforming interactions and activities. However, the rise of “Dark Patterns - deceptive design practices in websites and apps raises significant ethical concerns. Originally defined by User Experience Designer Harry Bringull, dark patterns manipulate users into actions like involuntary purchases and subscriptions. This study explored dark patterns on social media networking sites (SNSs), focusing on two key questions: Do platforms use specific dark patterns in combination, and how do these combinations impact user interaction and experience?Utilizing cognitive walkthroughs with UI/UX experts, this research examined dark patterns on YouTube, LinkedIn, Telegram, and WhatsApp. Researchers conducted platform-specific evaluations to examine and understand the various combinations of manipulative design elements. The findings revealed prevalent combinations of dark patterns and evaluated their effect, addressing a critical gap concerning social media's ethical implications in the Human-Computer Interaction (HCI) field. The findings contribute to disclosing ethical design practices and promoting a more user-friendly approach to UI design that enhances user well-being and trust in digital environments.